2011
DOI: 10.1111/j.1469-0691.2010.03405.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic aneurysm caused by Burkholderia pseudomallei: report of a Brazilian strain genetically related to Thai strains

Abstract: Melioidosis, a severe infectious disease caused by Burkholderia pseudomallei that is prevalent in Southeast Asia and Northern Australia, has been sporadically reported in Brazil since 2003. We report a case of aortic aneurysm with blood culture positive for B. pseudomallei. The phylogenetic analysis of 16S ribosomal DNA showed this isolate to be evolutionarily grouped with the MSHR346 strains from Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Presently, positive blood culture together with a radiological abnormality of the artery in the abdomen and pelvis (mainly on CT imaging) strongly suggests an infected mycotic aneurysm [19]. Herein, in our cases, at least one organ imaging abnormality was present in the intra-abdominal organs supplied by the abdominal aorta.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 47%
See 1 more Smart Citation
“…Presently, positive blood culture together with a radiological abnormality of the artery in the abdomen and pelvis (mainly on CT imaging) strongly suggests an infected mycotic aneurysm [19]. Herein, in our cases, at least one organ imaging abnormality was present in the intra-abdominal organs supplied by the abdominal aorta.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 47%
“…In 2011 the Institute for Communicable Disease Control and Prevention of China established a working group to monitor the epidemiology of melioidosis throughout China, revealing the overwhelming majority of culture-confirmed cases were from Hainan (99.0%, 392/396, 3 from Guangxi and 1 from Guangdong) between 2002 and 2016, and septicaemia was the most common clinical manifestation (153/277, 55.2%) [15].Taken together, the mycotic aneurysm cases collected in Hainan Province in the present study can represent the general epidemiological features in China. It is documented that most patients with infected mycotic aneurysm secondary to melioidosis are male and aged 60 years [1,2,12,19]. Similarly, in our case series, the ages of eight subjects ranged from 48 to 69, with a median age of 61.5 years, all were indigenous males, and two [24], Case 12-14 [25], Case 15 [26], Case 16 [3], Case 17 [27], Case 18 [28], Case 19 [29], Case 20 [30], Case 21 [31], Case 22 [19], Case 23-24 [6], and Case 25-26 [10], Case 27 [52], Case 28 [18], Case 29 [32], Case 30 [33], Case 31 [41], Case 32 [35], Case 33 [36], Case 34 [8] Case 35 [37], Case36 [38], Case37 [39], and Case38 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Melioidosis is particularly common in Northeast Thailand and ranks as the third most common cause of death from infectious diseases, only exceeded by HIV and tuberculosis 1. Despite increasing reports of melioidosis worldwide, the distribution and frequency of melioidosis is probably still greatly underestimated, especially in resource poor settings 2 6 7. Moreover, B. pseudomallei has a potential latency of infection and may present itself years after exposure 1…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only very few reports exist of mycotic aneurysms by B. pseudomallei in returning travellers without any established risk factors,14 15 but mycotic aneurysms have been described in travellers with risk factors16 and in endemic areas such as Australia,12 Southeast Asia4 8 17 and Brazil 7…”
Section: Discussionmentioning
confidence: 99%
“…Four siblings acquired acute infection after recreational exposure at the town dam and three of them died within a week [ 7 , 8 , 9 , 10 ]. By 2017, 30 cases had been diagnosed in Ceará [ 2 , 11 , 15 , 16 , 17 , 18 , 23 ]. Characterisation of clinical and environmental B. pseudomallei from Ceará showed that considerable genetic diversity is present [ 30 ].…”
Section: Review Of Published Melioidosis Cases and The Presence Ofmentioning
confidence: 99%